2014
DOI: 10.1128/iai.01972-14
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Immune Mechanisms Associated with Anemia in Plasmodium vivax Malaria: a Puzzling Question

Abstract: The pathogenesis of malaria is complex, generating a broad spectrum of clinical manifestations. One of the major complications and concerns in malaria is anemia, which is responsible for considerable morbidity in the developing world, especially in children and pregnant women. Despite its enormous health importance, the immunological mechanisms involved in malaria-induced anemia remain incompletely understood. Plasmodium vivax, one of the causative agents of human malaria, is known to induce a strong inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 147 publications
(75 reference statements)
1
29
0
Order By: Relevance
“…Plasmodium vivax is the most widely distributed species that cause malaria in humans, accounting for approximately 74.1% of the cases registered in the Americas in 2017 [1]. One of the major complications of P. vivax infection is anemia [2, 3], which is thought to arise from the destruction of both infected and non-infected RBCs [4]. Recently we have demonstrated that autoantibodies from P. vivax -infected patients are able to opsonize nRBCs, decreasing their deformability and increasing their in vitro phagocytic uptake, which may contribute to vivax malaria-associated anemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium vivax is the most widely distributed species that cause malaria in humans, accounting for approximately 74.1% of the cases registered in the Americas in 2017 [1]. One of the major complications of P. vivax infection is anemia [2, 3], which is thought to arise from the destruction of both infected and non-infected RBCs [4]. Recently we have demonstrated that autoantibodies from P. vivax -infected patients are able to opsonize nRBCs, decreasing their deformability and increasing their in vitro phagocytic uptake, which may contribute to vivax malaria-associated anemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…A dual role for specific antibodies against P. falciparum or P. vivax infection has been suggested for both immunity and pathogenesis of malaria (reviewed in [32]). Therefore, it was a reasonable hypothesis to investigate whether naturally acquired antibodies against conserved and variant PvMSP-1 proteins were associated with anaemia, a clinical parameter considered to be one of the major complications in P. vivax infections.…”
Section: Discussionmentioning
confidence: 99%
“…both INF γ and TNF α may induce dyserythropoietic anaemia 10 . In addition, the mechanisms involved in loss of bystander red cells are not clear 11 .…”
Section: Discussionmentioning
confidence: 99%